The Influence of Corporate Governance on Integrated Reporting Disclosure Moderated by Type Auditor - Afifah, Hasnaul; Surwanti, Arni; Pamungkas, Wihandaru Sotya (International Journal Labs, 2022)
The company's financial and non-financial statement information is likely to boost IRD's influence. Indonesia has not established guidelines for integrated reporting because it is still a novel concept for businesses and requires voluntary disclosure. The objective of this research is to the influence of independent board members, the board size, the female board, and the type of auditor on independent board members as a moderating variable on IRD. The sample in this study was the LQ45 Non-Banking on Indonesia Stock Exchange in the 2016-2020 period with a purposive sampling technique. The analytical tool used was Eviews 10 (x64). The result is independent board members have a positive effect and negative significance on IRD, board size has a positive effect on IRD, the female board has no effect on IRD, and the type of auditor no strengthens independent board members on IRD.